Manajemen Sumber Daya Manusia Pada Pendidikan Kader Ulama Di Yayasan Darul Fattah Lampung - Maulidina Aulia; Romlah; Sada, Heru Juabdin (Institut Agama Islam Darul Fattah Lampung, 2025)
The Ulama Cadre Education Program (PKU) at Darul Fattah Foundation in Lampung is a strategic effort to develop a generation of scholars who are morally upright, intellectually capable, and committed to sustainable da'wah, through the implementation of human resource management (HRM) based on Islamic values. This study employs a qualitative case study approach to explore how recruitment, selection, and development of educators are carried out in an Islamic and strategic manner. The findings show that recruitment is conducted internally through a recommendation system emphasizing the principles of amanah (trustworthiness) and kafa’ah (competence) selection is carried out through musyawarah syura (consultative deliberation) that considers spiritual aspects, and development is implemented continuously through a tarbiyah-based mentoring system covering knowledge, character, and responsibility in da'wah. A key finding of this study is the integration of modern HRM systems with Islamic principles, forming a spiritually grounded and sustainable model of HRM that can serve as a reference for Islamic educational institutions.